Influence Of Environmental Stressors On Plant Growth Plasticity Of Mimosa Pigra Towards Changes Of Soil Chemical Properties - Ali, Nur Zhafarina (2020)
The succession of invasive plants species is mostly facilitated by certain adaptive morphological and physiological traits. The establishment of Mimosa pigra seedling at early growth period, particularly in stressful environment is most crucial for the naturalization of this species. This species is assumed as either being able to maintain high fitness under unfavourable condition or has advantage over favourable environments, or both. As a legume plant, this species might has potential as soil enhancer despite of become exhaustive. To assess this, three manipulative stress growth conditions were imposed on M. pigra to specifically identify related traits enabling M. pigra invasiveness under stressful conditions and whether M. pigra expresses high adaptability mechanism in response to manipulative growth conditions. 1) Intraspecific competition (four similar size subplots were seeded with 25 g, 50 g, 75 g and 100 g of M. pigra seeds), 2) Initial light shading (seeds were grown under four different light gradient ranging from 25 to 75 % of ambient light) and 3) Short-term water stress (water withdrawal at different plant growth stages and restored after 12 days).